Cinematography. 65 mm and 70 mm. Sound. Specification for the reproduction characteristics of the A-chain frequency response for 70 mm motion-picture release prints with magnetic stripes Part 4.4.2, (15th July 1992) - British Standards Institution,
No abstract available